THE IMPORTANCE OF PROFESSIONAL COMPETENCIES IN THE HUMAN CAPITAL EFFECTIVE USAGE - Pavlovska, Valentina (SOCIETY. INTEGRATION. EDUCATION. Proceedings of the International Scientific Conference, 2015)
The research was done on how the effectiveness of human capital exploitation is influenced by the relevance of skills required by employer. The research problem: the mismatch of employee skills to employer’s requirements gives cause to an inefficient use of human capital, causing damage to both employers and employees. Study objective: To ascertain employees, working in the banking sector, skills, education and qualification compliance with industry requirements and determine how discrepancies affect employee motivation. The ability to make impartial self-appraisal of own activities and competences, is particularly important, because only a man who is able to impartially assess may plan the future, choose the right career directions, evaluate own characteristics, and identify cumbersome obstacles.